Pulmonary Alveolar Microlithiasis and Rheumatoid Arthritis: A Case Report and Review of the Literature - Hafiz, Waleed; Alahmed, Ahmedhusam; Alahmadi, Mohammed; Alotaibi, Rakan; Alsharif, Abdullah; Alim, Safwan; Mokhtar, Mohammed; Al-Maabdi, Kholoud; Badr, Omaima (Case Reports in Rheumatology, 2021)
Pulmonary alveolar microlithiasis is a rare autosomal recessive condition that is characterized by the formation of excessive calcium phosphate microliths in the alveoli. Most patients are diagnosed in adulthood due to the slow progression of the disease. Children with this disease are asymptomatic, and changes in the lung parenchyma are usually discovered incidentally. The diagnosis is made by the combination of a positive chest imaging and histological examination. Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease characterized by chronic seropositive symmetrical inflammatory polyarthritis with numerous extra-articular manifestations. It targets the lining of the synovial membranes, frequently affects females more than males, and is treated with the disease-modifying antirheumatic drugs (DMARDs). If left untreated, it leads to increased morbidity, mortality, and socioeconomic burdens. In this case, we report a 19-year-old young man who presented with clinical and radiographic features of PAM associated with RA.